Measurement of Indoor Thoron Gas Concentrations Using a Radon-Thoron Discriminative Passive Type Monitor: Nationwide Survey in Japan - Tetsuya Sanada (International Journal of Environmental Research and Public Health, 2021)
As part of a nationwide survey of thoron (220Rn) in Japan, the indoor 220Rn gas concentrations in 940 dwellings were measured throughout one year, from 1993 to 1996, using a passive type 222Rn-220Rn discriminative monitor. The monitor was placed in a bedroom or a living room in each house for four successive three-month periods. The mean annual indoor 220Rn concentration was estimated from the four measurements in each house. The arithmetic mean, the median and the geometric mean for indoor 220Rn concentrations in 899 dwellings were 20.1, 9.6 and 10.0 Bq m−3, respectively. The 220Rn concentrations exhibited a log-normal distribution. It was found that the 220Rn concentrations were dependent on the nature of the materials used for wall construction and also on the distance of measurement from the wall. Significant seasonal variations in the 220Rn concentration were not observed. It would seem that the nature of the wall material contributed to the increased indoor 220Rn concentrations.